Analisis Diagnosis Tuberkulosis Paru Pasien Rawat Inap Bulan November 2023 di RSUD Banyumas - Najwa Azkia Rahma; Zahrasita Nur Indira; Harry Fauzi; Utami Budi Lestari (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2024)
According to the World Health Organization (WHO) in the Global Tuberculosis Report 2021, TB is one of the 10 causes of death in the world. The Ministry of Health of the Republic of Indonesia recorded a total of 658,543 TB cases in 2023 as of November 3, 2023. At Banyumas Hospital, TB cases are still relatively high, the factors that affect this pulmonary TB are clinical factors. The research was made to determine the clinical factors of Pulmonary TB disease and supporting examination factors in determining the success of claims at Banyumas Hospital. This type of research method uses quantitative, with analytical descriptive research design, and cross sectional research design. The type of data used is secondary data, namely medical record data for inpatients with pulmonary TB, Data analysis using Univariate which describes the percentage of Pulmonary TB. The total number of TB patients had 43 medical records in November 2023 at Banyumas Hospital, the result of the percentage of male sex factors (62.79%) Female (37.21%), the most OAT-giving factor RHZE (76.74%), the most age factor for the elderly (30.23%). Supporting Factors for positive TCM reading (48.83%) and RO factor Thorax pulmonary TB reading (93.02%). The advice from this study is to monitor TB patients to regularly take OAT so that they never break up for 6 months.